-2/3*(6/7-x)+(2/7+x) -(x+1/8)+3/4*(2+x)
7/8*(4-x)-(3/4+x)
-(3/19-x)-1/2(x+2/19)
-7/13*(26/27+x)-(4/9-x)

сделайте всё что сможете​

4ev43yi3 4ev43yi3    1   01.08.2021 18:23    0

Ответы
privetloll privetloll  31.08.2021 20:01

Пошаговое объяснение:

1)

= -2/3 * 6/7 - (-2/3х) + 2/7 + х =

-12/21 + 2/3х + 2/7 + х =

-4/7 + 2/3х + 2/7 + х =

1. 2/3х - 2/7

2)

= -х - 1/8 + 3/4 * 2 + 3/4х =

-х - 1/8 + 6/4 + 3/4х =

-х - 1/8 + 12/8 + 3/4х =

-1/4х + 11/8 = -1/4х + 1. 3/8

3)

= 7/8 * 4 - 7/8х - 3/4 - х =

28/8 - 7/8х - 6/8 - х =

-1. 7/8х - 22/8 =

-1. 7/8х - 2. 6/8 =

-1. 7/8х - 2. 3/4

4)

= -3/19 + х - 1/2х - 1/2 * 2/19 =

-3/19 + х - 1/2х - 1/19 =

1/2х - 4/19

5)

= -7/13 * 26/27 - 7/13х - 4/9 + х =

-7/1 * 2/27 - 7/13х - 4/9 + х =

-14/27 - 7/13х - 4/9 + х =

-14/27 - 7/13х - 12/27 + х =

6/13х - 26/27

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика